PENGARUH TINGKAT PENDIDIKAN TERHADAP TINGKAT PENGETAHUAN MASYARAKAT TENTANG PENGOBATAN SENDIRI (SELF MEDICATION) DI WILAYAH KABUPATEN SLEMAN JOGJAKARTA - Nanang Munif Yasin (Jurnal Ilmiah Farmasi, 2004)
A B S T R A C TThe motivation for taking self medication increased as well as the growth of drugsproduction in Indonesia. Self medication will taking a risk, so that it must be followed by the enoughsociety knowledge about medicine. The research about an Influence of Education Level to theSociety Knowledge Level about Self Medication in Sleman Yogyakarta had been done. Thisresearch tried to shoot the society knowledge level about the aspects corelated with self medicationand an influence between the education level increased to the society knowledge level about selfmedication. From this research, can be hopen that the problems about irrasional drug using in selfmedication will be decreased. A sample that had been used is the society in Sleman Yogyakarta.The sample had been taken by stratified random sampling. This research was explorative and thedata had been gotten by quisioner and interview. The analysis of data had been done by thedescriptive statistic analysis and interferention analysis. The result showed that there was asignifican difference between education level with medium and high education level aboautknowledge of self medication. Mean value were 63,35 ± 7,27 ; 68,56 ± 6,29 ; dan 68,69 ± 7,72 .The difference specially about drugs classification, side effect of drugs and characteristic of drug.The result showed that if the eduacation level increased, the society knowledge level about selfmedication will be increased.Key word : drug, self medication, knowledge, education level